The effect of corporate governance on earnings management moderated by political connection - Rini Adriani Auliana; Bambang Subroto; Imam Subekti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This research aims to prove the effect of independent commissioner performance and audit committee expertise on earnings management to avoid earnings decreases and political connections to strengthen independent commissioner performance and audit committee expertise to limit earnings management.Design/Methodology/Approach: The population was manufacturing firms listed on Indonesian Stock Exchange during 2017-2020. The sampling technique used purposive sampling with a sample of 102 firms for four years or 408 observations. Then, hypothesis testing employed multiple regression analysis and hierarchical regression analysis.Research findings: The results showcased that accrual earnings management and abnormal discretionary expenses were used by managers to avoid decreases in earnings. On the other hand, corporate governance, like audit committee expertise, could be used to limit earnings management. While the political connection could strengthen and weaken the effect of independent commissioner performances in limiting earning management, political connections could not strengthen audit committee expertise in limiting real and accrual earnings management.Theoretical contribution/Originality: This research contributes to the political connection and earning management literature and provides empirical evidence of agency theory, positive accounting theory, prospect theory, and resource dependence theory.Practitioner/Policy implication: This research contributes to investors in determining investment decisions.Research limitation/Implication: The limitation of this research is that independent variables only used two components of corporate governance, i.e., the independent commissioner performances and audit committee expertise, so the level of influence of the independent variables on the dependent was small.